Rhinitis and pregnancy: literature review - Caparroz,Fábio Azevedo (2016)
ABSTRACT INTRODUCTION: There is a controversy concerning the terminology and definition of rhinitis in pregnancy. Gestational rhinitis is a relatively common condition, which has drawn increasing interest in recent years due to a possible association with maternal obstructive sleep apnea syndrome (OSAS) and unfavorable fetal outcomes. OBJECTIVE: To review the current knowledge on gestacional rhinitis, and to assess its evidence. METHODS: Structured literature search. RESULTS: Gestational rhinitis and rhinitis "during pregnancy" are somewhat similar conditions regarding their physiopathology and treatment, but differ regarding definition and prognosis. Hormonal changes have a presumed etiological role, but knowledge about the physiopathology of gestational rhinitis is still lacking. Management of rhinitis during pregnancy focuses on the minimal intervention required for symptom relief. CONCLUSION: As it has a great impact on maternal quality of life, both the otorhinolaryngologist and the obstetrician must be careful concerning the early diagnosis and treatment of gestational rhinitis, considering the safety of treatment measures and drugs and their current level of evidence.